Classification of Dad Jokes in icanhazdadjoke.com - Rosyad Mahasin Miranto (The English Department, Faculty of Languages and Arts, Universitas Negeri Surabaya, 2020)
Dad Jokes is a short joke, typically a pun, presented as a one-liner or a question and answer, but not a narrative. Dad Jokes is actually treated as an entirely separate thing compared to puns or word plays, even though puns make up the majority of the joke. Of course, the name “Dad Joke” is derived from the fact that it is usually been told by one’s own father. This Study uses various Theories, such as Jensen’s Explanation of Dad Jokes (2015), as well various theories for Sentence Structure, Puns, Semantic Relation, Figure of Speech, and most notably, Searle’s Theory of Illocutionary Act (1977). The Method used in the study is Quantitative. The Data here are gathered and classified based on numbers, percentage, and statistics, both for the classification of the subject as well as the analysis of the Dad Joke. As for the Subject, there are a total of 540 examples of Dad Jokes from icanhazdadjoke.com. The Datas are gathered from Icanhazdadjoke.com before its individual jokes are going to be analyzed, in order to understand how Dad Jokes are groupe. The full analysis would take too long to mention, however, and thus only its results are explained here with some examples. In the end, as a result of this study, Dad Jokes are divided into three forms of Classifications, consisting of Four Types by the Structure, Six Types by the Meaning, and Five Types by the Illocutionary Act. Key Words: Dad Jokes, Classification, Puns and Wordplays, Illocutionary Act